KERENTANAN EMPAT JENIS KAYU RIMBA TERHADAP SERANGAN JAMUR PEWARNA - Dominicus Martono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
This study evaluates the susceptibility of ramin (Gonystilus bancanus Kurz), jelutung (Dyera sp), mentibu (Dacty- locladus stenostachys Oliv) and meranti batu (Shorea sp) against sapstain. The material used consists of debarked and unbarked fresh logs. The tested logs were tried at swamp forest in West Kalimantan in November - December 1978.The data were analysed by Nested Classification method. The degree of damage was transformed into arcsin √%Inspections were conducted biweekly for one month after treatment.The result showed that the average degree of damage due to the sapstain were not different among the four wood species. The effect of debarking treatment increases the log susceptibility. There is no different of staining degree among the log cutting from the base, middle and top of the trees.